2016
DOI: 10.1001/jama.2016.16146
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Payment Reform in Medicare

Abstract: Cardiovascular disease is the leading cause of death and disability in the United States, accounting for 1 in 4 deaths and more than $200 billion in direct and indirect costs annually. 1 In July 2016, the Centers for Medicare & Medicaid Services (CMS) proposed a new episode-based payment model for myocardial infarction. This model aims to improve the quality and efficiency of cardiac care and helps move the United States toward CMS's goal of having 50% of traditional Medicare payments in valuebased models by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Many episode-based payment models are structured around a time period only a few weeks to months after treatment to encompass acute and subacute treatment-related complications. 2426 The Centers for Medicare and Medicaid Services Oncology Care Model is the latest iteration of a specialty-based global payment system that encompasses a 6-month period of care after the initiation of chemotherapy. 27 However, our study suggests that this approach may be insufficient for radiotherapy-centric episodes because cost savings as a result of decreased toxicity from more advanced radiation techniques may require a longer time period to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many episode-based payment models are structured around a time period only a few weeks to months after treatment to encompass acute and subacute treatment-related complications. 2426 The Centers for Medicare and Medicaid Services Oncology Care Model is the latest iteration of a specialty-based global payment system that encompasses a 6-month period of care after the initiation of chemotherapy. 27 However, our study suggests that this approach may be insufficient for radiotherapy-centric episodes because cost savings as a result of decreased toxicity from more advanced radiation techniques may require a longer time period to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] More than 600,000 deaths (1 in 4) are attributable to heart disease each year, and CVD accounts for more than $70 billion annually (approximately 17% of the total health care expenditure). [56][57][58] By the year 2030, 40% of the US population is projected to have some form of CVD, and care will exceed $800 billion, making it our most costly disease. 56 The understanding of the pathogenesis of atherosclerosis has recently undergone a dramatic update.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Payment reform is a tool to improve the quality and consistency of patient care, while also reducing unnecessary costs. Cardiovascular disease draws attention for new payment models primarily because it accounts for more than $200 billion in annual spending 1 . One such model, “Advancing Care Coordination through Episode Payment Models” (EPM), was an initiative of the Centers for Medicare and Medicaid Services (CMS).…”
Section: Policy Contextmentioning
confidence: 99%
“…This may have measurable effects on hospitals with different case mixes, such as referral centers for STEMI. The resulting adverse incentives may lead to risk-averse behavior by hospitals, with selection bias influencing treatment decisions within participating hospitals 1 . Predictive cost analysis models have demonstrated that hospitals that care for sicker patients with fewer financial means may perform worse in this payment model 13 .…”
Section: Lessons For Future Cardiac Epmsmentioning
confidence: 99%